2010
DOI: 10.1021/ef901215m
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of Carbohydrates in Ionic Liquids

Abstract: While carbohydrates serve as an abundant, diverse, and reusable source of carbon, their derivatization for industrial applications is still a challenging task because of the low solubility in solvents other than water. Ionic liquids are recognized as green solvents for carbohydrate processing. However, only a limited number of studies have been carried out to investigate their ability to dissolve and modify saccharides. Most of the works focus on cellulose. The aim of this Review is to assess the current state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
328
1
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 481 publications
(334 citation statements)
references
References 63 publications
3
328
1
2
Order By: Relevance
“…27, 28 The application of ionic liquids in carbohydrates (lignocellulosic biomass) chemistry is relatively new and further studies combining these two fields are presented by Zakrzewska et al 29 Additionally, Qi et al also reported promising results when they studied the production of HMF from glucose and fructose catalyzed by TiO 2 and ZrO 2 under microwave irradiation.…”
Section: -23mentioning
confidence: 99%
“…27, 28 The application of ionic liquids in carbohydrates (lignocellulosic biomass) chemistry is relatively new and further studies combining these two fields are presented by Zakrzewska et al 29 Additionally, Qi et al also reported promising results when they studied the production of HMF from glucose and fructose catalyzed by TiO 2 and ZrO 2 under microwave irradiation.…”
Section: -23mentioning
confidence: 99%
“…In all these treatments, the substantial degradation of lignin is accompanied by considerable reduction in fermentable sugar content of the feedstock, resulting in a loss of 20-35% of the mass of lignocellulose (Galbe and Zacchi 2007;Lee et al 2009). In contrast, recent reports give ample evidence that pretreating biomass with ionic liquids can disrupt the interactions between plant cell wall polymers, resulting in significant improvements in enzymatic hydrolysis kinetics while preventing the loss of fermentable sugars and facilitating the fractionation of biomass (Cheng et al 2011;da Costa Lopes et al 2013;Li et al 2010;Li et al 2009;Mora-Pale et al 2011;Singh et al 2009;Zakrzewska et al 2010;Zavrel et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14] Because of the high solvating ability for biomaterials, ILs have been extensively explored for the deconstruction of biomass, particularly lignocellulosic and cellulosic materials. [15][16][17][18][19][20][21] ILs as cellulose dissolving solvents have been critically reviewed in Tom Welton's research group very recently. 22 Apart from cellulosic materials, the dissolution/regeneration of chitin/CH or AG has also been carried out in ILs, and useful materials have been prepared from these polysaccharides [23][24][25][26][27][28][29][30][31] (Note: there are many other biomaterials which have been treated with ILs but not referred to here as the present study intends to focus on AG and CH).…”
Section: Introductionmentioning
confidence: 99%